1999
DOI: 10.1179/000705999101500923
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical screening of organic inhibitors for corrosion of UNS N0400 in saturated monoethanolamine solution

Abstract: In response to environmental concerns associated with the buildup of arsenic sludge used in A. AL-HASHEM the monoethanolamine (MEA) CO 2 removal unit at a refinery in Kuwait, two organic based J. A. CAREW inhibitors have been evaluated as potential replacements for the inorganic sodium arsenate A. HASAN used earlier. T he inhibitors were evaluated for UNS N0400 (Monel 400) in f resh MEA solution saturated with an 85H 2 -15CO 2 gas mixture at 40°C using electrochemical impedance spectroscopy, potentiodynamic po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…This was thought to be due to the presence of substituted groups which prevented the inhibitor from lying flat on the steel surface. Similarly it was found that in 18 per cent monoethanolamine solution (saturated with 8 per cent H 2 S, 15 per cent CO 2 ), an amide based inhibitor (66 per cent efficiency), was more effective than an amine type (15 per cent efficiency), in reducing the corrosion rate of UNS400 steel at 40 C (Al-Hashem et al, 1999).…”
Section: Electronic Accessmentioning
confidence: 89%
“…This was thought to be due to the presence of substituted groups which prevented the inhibitor from lying flat on the steel surface. Similarly it was found that in 18 per cent monoethanolamine solution (saturated with 8 per cent H 2 S, 15 per cent CO 2 ), an amide based inhibitor (66 per cent efficiency), was more effective than an amine type (15 per cent efficiency), in reducing the corrosion rate of UNS400 steel at 40 C (Al-Hashem et al, 1999).…”
Section: Electronic Accessmentioning
confidence: 89%
“…Perhaps one of the most important features of biofilms is that under-biofilm conditions could be far different from the bulk solution in almost all respects; for instance, by typically reaching a thickness of 12 micrometres, the under-biofilm environment will become anaerobic (oxygen-free) [7]. In fact, under-biofilm factors such as pH, dissolved oxygen, etc.…”
Section: Some Important Features Of Biofilmmentioning
confidence: 99%